CROSS-SECTION GENERATION OF VARIOUS GEO-SCIENTIFIC FEATURES WITHOUT CONTOUR DIGITIZATION USING A VISUAL C++ BASED SOFTWARE APPLICATION ‘VIGAT 2005’ - Dasgupta A. R.; Solanki Ajay M.; Rathod Brijesh G.; Srivastava Naveenchandra N.; Patel Vivek R.; Machhar Suresh P. (Earth Sciences Research Journal)
Cross-section can be described as a two dimensional dataset where the horizontal distances are represented on the x-axis and the depth on the y-axis. A cross-section is a window into the subsurface. This work presents the construction of cross sections with the help of 'Vigat 2005' - a Visual C ++ based software application. Its main purpose is to provide cross section views of geoscientific features and to interpret their variation within the area of study. In geological context, profile or cross section is an exposure of the ground showing depositional strata. Geological cross sections are very powerful means of conveying structural geometries. They are planar, usually vertical, graphical representations of earth sections showing stratigraphical successions, age, structure, and rock types present in the subsurface. Geological cross sections allow a better conceptualization of the 3-D geometry of the structures. By using 'Vigat 2005', a cross section graphic can be displayed by the user with a simple click of the mouse. It offers much easy to use functionality to facilitate the completion of desired tasks. Specific boundary conditions to represent the movement of rock block over the fault can be displayed using the graphical user interface. Relief or slope variation of the study area can also be viewed. A topographical map provides an aerial (overhead) view of a landscape. It is possible to create a more pictorial representation of the landscape by making a topographic profile of the region. A topographic profile is a cross section showing elevations and slopes along a given line. A precise method to determine slope variations is to construct a profile or cross section through the topography. The most important advantage of 'Vigat 2005' is that users do not need to digitize contours. This work focuses on the design and implementation of an optimized interpretive environment that have been built using Visual C++ tools. Strong programming capabilities of Visual C++ have been utilized, at its full extent, for the development of 'Vigat 2005'.